Assessment of regional spatial plan (RSP) of areas along the active fault of Seulimeum segment in Aceh Province. Issue 1 (February 2021) - Darmi, A; Ismail, N; Aulia, T B; Nanda, M; Yanis, M
Abstract: The Seulimeum Segment is the northernmost branch of the Great Sumatran Fault. This active fault crosses settlements in Aceh Besar Regency and Pidie Regency in Aceh Province. Tectonically, this situation can be a threat along the active fault line. In this study, active fault lines of the Seulimeum Segment were mapped. Based on the active fault lines, residential areas, infrastructure distribution, and Regional Spatial Plan (RSP) were reviewed for eligibility. Some areas, e.g., Tangse, Lamtamot, and Krueng Raya, were the focus of this study. Avoidance zones were categorized based on their distances from the active fault line, which were 20 m from the fault, 100 m from the fault, and 300 m from the fault. According to an active fault line analysis on the RSP map, infrastructure map, and demographics map, the Krueng Raya area would be the most affected by losses due to disasters in the future. Some buildings, hospitals, mosques, government offices, settlements, and industrial areas in Krueng Raya are situated along an active fault line. It is because the RSP of this area has not yet considered the potential for geological disasters in the infrastructure development process. Some recommendations have been proposed to reduce the impact of losses in the future.